(untitled) (Journal of history, 2025)
The article is devoted to the study of the fate of child homelessness in Western Kazakhstan during the famine of 1921-1923, the history of the creation and activities of orphanages. During the years of famine, the number of children left without parental care was in the thousands. The purpose of the work is to conduct a historical and comparative analysis of the consequences of children being left without care and attention on the street due to hunger. Specific objectives of the study are a comparative analysis of the history of street children using archival documents, census materials and statistical data, as well as the use of statistical analysis methods. Consequences of famine in the West Kazakhstan region, the extent of damage and their impact on the lives of children. A feature of the research methodology is the systematization of statistical data on child homelessness by various dimensions and modules. The activities of the orphanage, the use of funds allocated by the state for relevant activities, and the material condition of the orphanage are considered. The results of the study showed that the use of the comparative method in studying the demographic consequences of child homelessness due to famine contributes to a more in-depth study of this topic. The results of the qualitative analysis using statistical data were the empirical basis for creating a complete demographic picture of the famine in Kazakhstan in the 1920s in the lives of children